Optimization of substrates for conidia production of Trichoderma harzianum By Solid Fermentation in the region of San Martín. Peru - Arévalo, Enrique (2017)
In order to optimize alternative substrates to whole rice grain of good quality for the production of Trichoderma harzianum conidia, mixtures of agricultural residues (rice husks whole, rice husks crushed and peanut husks) were carried out with crushed rice Known as Ñelen and nutrient sources such as water, urea and calcium carbonate (CaC03 ) to select the best substrate in which to obtain the largest number of viable conidia under a completely random design, with 14 treatments and three replicates. The production was carried out in two phases; production of inoculum by liquid fermentation and massive production of conidia by solid fermentation. The number of conidia per gram of substrate, percentage of germination and purity was evaluated. The production of conidia of T. harzianum was superior to 1x1010 conidia. g-1 substrate in the agricultural residues that were mixed with Ñelen, statistically surpassing the conventional substrate (whole rice grain). The highest concentration of conidia was in the treatment T7 (whole rice husk + Ñelen) continued T8 (ground rice husk + Ñelen) and T9 (peanut shell + Ñelen) enriched with urea. Likewise, germination percentage of T. harzianum conidia showed levels higher than 85%, being the treatments enriched with water with values of germination ≥ 90%. Therefore, all treatments were 100% pure, indicating that they are accepted by quality standards and represent a better option for the production of this fungus.